AMYLOID BETA PEPTIDES AS ANTIMICROBIAL PEPTIDES: RELEVANCE FOR ALZHEIMER’S DISEASE? - Karine, B. (Innov Aging, 2017)
Amyloid β (Aβ) peptides generated by the amyloidogenic pathway of amyloid precursor protein (APP) processing contribute significantly to neurological degeneration characteristic of Alzheimer’s disease (AD). Their precise role, whether it be direct or the indirect target of an inflammatory response, has been a subject of considerable debate. Data published in the last 6 years by three different groups have added a new twist by revealing that Aβ peptides could act as antimicrobial peptides (AMP). These observations are of significance with respect to the notion that pathogens may be important contributors to the development of AD, particularly in the case of Herpes simplex virus (HSV) infection which often resides in the same cerebral sites where AD arises. Our recent data support the interpretation that Aβ peptides behave as AMP, with an emphasis on studies concerning HSV-1 and a putative molecular mechanism that suggests that interactions between Aβ peptides and the HSV-1 lead to impairment of HSV-1 infectivity by preventing the virus from fusing with the plasma membrane.